Analysis of Cosmic Rays from Inter-Electronic Structure of the Electron-Revised Version - Nandedkar, Dr. Deepak (Recent Advances in Properties of ‘Physics/Electrical Engineering’ Materials, 2022)
Here an analysis of cosmic rays from inter-electronic structure of the electron is reconsidered with respect to a previous paper by Nandedkar, where electromagnetic nature of cosmic rays is analyzed along with complex charge and complex mass of an electron. Here it is interesting to note that the moving mass of the electron inside and / on periphery of the electron has a velocity of 4.239(4)×108 m/sc which is greater than velocity of light in free space. Thus a world of Tachyon (where particle velocity can exceed velocity of light in free space) exit inside and / on periphery of the electron. In this paper strength of magnetic flux density required for reversal of spin angular momentum is reconsidered with real part of complex charge, of the moving electron along periphery of the circle of electron having radius of 1.878(8)×10-15 m, illustrating spin of the electron diagrammatically. This electron radius of 1.878(8)×10-15 m called "reduced radius" is (2/3) times so called "classical radius" of electron. Distribution of complex charge and complex mass of the electron is confined to the circle of "reduced radius" of the electron. Strength of magnetic flux density required for reversal of spin angular momentum is 1.877×1014 Wb/m2. Sudden alternate reversals of magnetic flux densities in this case of equal to or greater than above value, generate continuous waves of cosmic rays of frequency 1.795(6)×1022 Hz by complex mass/ complex charge inter-electronic structure, which is reconsidered.